ANALISIS PRIORITAS DAN STRATEGI LAYANAN TRANSPORTASI PERIKANAN TANGKAP DI PELABUHAN PERIKANAN NUSANTARA AMBON (Torani Journal of Fisheries and Marine Science, 2016)
A fishing port is expected to be functioning if the port is able to provide services and facilities to smoothing theproduction, processing and marketing processes invarious aspects. This study was aimed to determine factors tobe considered and expected to influence the transportation system services and to reveal the strategies and theirpriorities to improve the services. The research was conducted at PPN Ambon in Maluku Province. AnalyticalHierarchy Process (AHP) and SWOT Analyses were applied to analyze the data. The study reveals that theinfrastructure, accessibility, the fishing boat, the basic facilities, boat size, the fishing unit, licensing system, andthe education of the personnels were found to be in the high priority. Strategies to be implemented are needed tobe emphasized on the external access to the industrial area, water supply, fuel oil, and ice supply. Keywords: priority, strategy, services, capture fisheries,PPN Ambon.